Eros Figures in the Iconography of Death: Some Notes on Funerary Monuments from Macedonia during the Roman Period - Aristodemou, Georgia (Eikón / Imago, 2021)
This paper discusses the intense presence of Eros figures in funerary monuments from the region of Macedonia during the roman period, evolving around the perception of death, the familial bonds and social structure that these monuments reveal. Eros, depicted either leaning on or holding an inverted torch, or sleeping on a rock, when placed upon graves is perceived as Eros funéraire. The funerary connotations of Eros figures often assimilate them with Sleep, Death, and the eternal sadness of Death. Especially when used in the funerary monuments of children, these figures accentuate the parental grief for the loss of their children. On the other hand, the childlike representation of Eros symbolizes the eternal beauty of youth and the parental hope that their deceased children will continue enjoying a happy afterlife.